Downsizing the civil service in developing countries: golden handshakes or smiling farewells? - Peters, Lucien (1998)
Some researchers have suggested innovative ways to successfully implement civil service reform in developing countries. Although most approaches to implementing public sector management reform are still very much process-driven, and focus almost exclusively on civil service reform, long-term success in making the public sector more efficient may be better assured if civil service reform is but one outcome of a broader public sector management reform agenda. Particularly, re-focussing from traditional input-driven reform thinking towards output-oriented measures, such as the introduction of accrual budgeting in the public sector, may well result in greater popular acceptance and, thus, longer-term success for sensitive reform programs. Although output-driven accrual budgeting is by no means a panacea for all public sector illnesses, it can at least set the scene for profound and durable cultural change in the public sector. - Reproduced
Keywords: Civil service - Developing countries; Administrative reform